5-year disease progression of patients across the glaucoma spectrum assessed by structural and functional tools. Issue 6 (22nd September 2017) - Seth, Natasha Gautam; Kaushik, Sushmita; Kaur, Savleen; Raj, Srishti; Pandav, Surinder Singh
Abstract : Background: Assessment of spectral-domain optical coherence tomography (SD-OCT) compared with visual fields, to detect progression across the glaucoma spectrum. Methods: In this study, adult glaucoma suspects and patients, with baseline retinal nerve fibre layer (RNFL) thickness on SD-OCT and reliable visual field (VF) tests on Humphrey Field Analyser (HFA) prior to March 2010, were recruited. Functional and structural progression over at least 5 years was compared using Glaucoma Progression Analysis (GPA) and VF index (VFI) on HFA and Guided Progression Analysis (GPA-OCT) on SD-OCT, respectively. Agreement of progression detection between the two modalities was computed using κ statistics. Results: 122 subjects (63 glaucoma suspects; 59 glaucoma patients) were enrolled. Of 18 suspects who progressed to glaucoma, 13 showed progression by GPA-OCT, 4 by GPA, 7 by VFI and 2 were concordant. In the 14 glaucoma patients who progressed, GPA-OCT detected progression in 6, GPA in five and VFI in six. GPA-OCT had poor agreement with GPA in glaucoma suspects (Kappa 0.15; p=0.13) and patients (Kappa 0.10; p=0.45). VFI had better agreement with GPA-OCT in glaucoma suspects (Kappa 0.34; p=0.01) than glaucoma patients (Kappa 0.12; p=0.36). Progressors by VF in both groups had similar percentage change from baseline RNFL thickness (−9.9% vs −8.6% p=0.46), even though the absolute change was significantly greater in suspects(−8.75µ vs−6.4µ p=0.03). Conclusion: Structural change appears to be more useful to detect progression in glaucoma suspects, while functional change is a better indicator as the disease progresses. Percentage change from baseline RNFL thickness was a better measure than absolute change in RNFL.